Is the law of reflux valid? - Per Hortlund (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
In the classical monetary debates, the Banking School held that notes would be equally demand-elastic whether supplied by many or a single issuer. The Free Banking School held that notes would be less demand-elastic if supplied by a single issuer. These assertions have rarely, if ever, been subject to more stringent statistical testing. In this paper I compare the elastic properties of the note stock of the Swedish note banking system in 1880-1895 with those of the regime in 1904-1913, when the Bank of Sweden held a note monopoly. Evidence suggests that notes did not become less elastic after monopolisation, thus lending support to the views of the Banking School.
Keywords: B12; E42; E51; E58; N13; N23; 330; Banking School; Free Banking School; Elastic currency; Clearing mechanism; Needs of trade; Law of Reflux; Real bills doctrine; Banking-Schule; Free Banking; Verrechnungsverkehr; Geldmenge; Zentralbank; Geldangebot; Monopol; Schweden